An Empirical Investigation of Crowdfunding as an Instrument for Financing Entrepreneurial Start-ups successfully - Sharma, Upasana (2014)
The aim of this dissertation is to review the obstructions faced by the young entrepreneurs and the early start-ups to acquire finance and thereby explore the novel phenomenon of “crowdfunding”. Crowdfunding is still in its evolutionary flux and has developed limited academic literature so far. Thus, the research structures by first reviewing the literature on this new concept based on the problems faced by new ventures. Second, several project campaigns selected from popular crowdfunding platforms: Kickstarter and Indiegogo are evaluated. Then,a model using the grounded theory method is conducted in which the empirical investigation intends to bring out the three factors- social entrepreneurship, commercial entrepreneurship and problem solving that influence the innovative success factor of crowdfunding campaign that helps raising startup capital effectively. This model so constructed is named ‘the crowdfunding innovative success model’. Lastly, the prospects of future research are discussed. Keywords: young entrepreneurs, social media, web 2.0, crowdfunding, innovative success, social and commercial entrepreneurship, problem solving.